Ezobudoda (manhood things) a qualitative study of HIV-positive adolescent boys and young mens health practices in the Eastern Cape Province of South Africa - Gittings, Lesley Blinn (Department of Public Health and Family Medicine, 2020)
Men are less vulnerable to HIV acquisition than women, but have poorer HIV-related outcomes. They access HIV services less often and later, and are more likely to die while on antiretroviral therapy (ART). The adolescent HIV epidemic presents further challenges, and AIDS-related illness is the leading cause of death among adolescents in sub-Saharan Africa. Such deaths have tripled since 2000, while declining in all other age groups. There is a clear need to better understand health practices for adolescent boys and young men living with HIV, and the processes through which these practices are formed and sustained. This doctorate explores the biosocial lives of adolescent boys and young men living with HIV in the Eastern Cape Province of South Africa. It engaged health-focused life history narratives (n=36), semi-structured interviews (n=32) and analysis of health facility files (n=43), alongside semi-structured interviews with traditional and biomedical health practitioners (n=14). Young male participants were among the first generation to grow up with access to ART and democratic freedoms. In a context where HIV-positivity and men’s inability to fulfil traditional roles are considered signs of social and moral decay, they felt pressure to be ‘good’ HIV-positive patients and respectable young men. As younger children, they performed to norms of HIVpositive patienthood. As they became older, norms of masculinity, including financial achievement, ulwaluko (traditional initiation/circumcision), ‘moral’ behaviour and engaged fatherhood became more important and began to conflict with performances of ‘good’ patienthood. This was most apparent during and following ulwaluko, where societal norms made it difficult to engage with biomedical treatment and care. Despite this, participants and their families demonstrated agency, creativity and resilience in subverting and re-signifying these norms. Participants did not access traditional products or services for HIV-related issues, a finding that deviates from much of the literature. This study suggests that health practices are mediated not only by gender and culture, but also childhood experiences of growing up deeply embedded in the health system, through which participants forged additional health-seeking tools. Findings affirm the syncretic nature of traditional beliefs, documenting the plural and complementary ways that participants engaged with traditional products and services.